2021
DOI: 10.3389/fendo.2021.667773
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Glycerol-3-Phosphate Acyltransferases 4 and BDNF in the Progress of Obesity-Induced Depression

Abstract: BackgroundObesity has been reported to lead to increased incidence of depression. Glycerol-3-phosphate acyltransferases 4 (GPAT4) is involved in triacylglycerol synthesis and plays an important role in the occurrence of obesity. GPAT4 is the only one of GPAT family expressed in the brain. The aim of this study is to investigate if central GPAT4 is associated with obesity-related depression and its underlying mechanism.ResultsA high-fat diet resulted in increased body weight and blood lipid. HFD induced depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…On the other hand, some pro‐inflammatory agents (IL‐8, TNF‐α, IL‐6, IL‐17, IL‐1β, and ICAM‐1) were found to be modulated by EP3 in this research. As we know, CREB could mediate the pro‐inflammatory cytokines 43,44 . Thus, it can be concluded that EP3 promoted the inflammatory responses through up‐regulation of CREB.…”
Section: Discussionmentioning
confidence: 93%
“…On the other hand, some pro‐inflammatory agents (IL‐8, TNF‐α, IL‐6, IL‐17, IL‐1β, and ICAM‐1) were found to be modulated by EP3 in this research. As we know, CREB could mediate the pro‐inflammatory cytokines 43,44 . Thus, it can be concluded that EP3 promoted the inflammatory responses through up‐regulation of CREB.…”
Section: Discussionmentioning
confidence: 93%
“…The former is targeted by three drugs with antineoplastic activity which decrease its expression: doxorubicin 52 , 59 , orlistat 60 , 61 , and paclitaxel 60 , 62 . GPAT4 is the only gene of the GPAT family expressed in the brain, and it has recently been identified as a potential drug target for treating obesity-associated depression 63 .
Figure 4 Comparison of genes of interest identified in this study against published works: ( A ) Larsson et al 56 , which highlighted essential genes for models for high and low survival, ( B ) Richards et al 9 , where the list of marker genes comprises the top 50 genes for each one of the 86 intra-GSC clusters, ( C ) Wang et al 54 , where upregulated genes for outer RG-like and ventricular RG-like (UP ORG and UP VRG, respectively) were considered, and ( D ) Liu et al 67 , where “targets” comprise both genes and miRNAs.
…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, depressive mood may occur in adolescents with obesity due to biochemical changes caused by metabolic disturbances, including expanded cerebrospinal fluid space and diminished white matter volume [ 27 ]. Furthermore, neurodegeneration and structural remodeling may impair emotion, study and memory through brain inflammation [ 40 ], and mostly affected the hippocampus [ 40 ]. A major component of the MUHO definition consisted of inflammation in the majority of previous studies.…”
Section: Discussionmentioning
confidence: 99%